Answer:
If you are talking about y=
then the graph would be Graph A.
Answer:
6
Step-by-step explanation:
All you have to do is divide -4 on both sides and you get 6!
-4x= -24
/-4 /-4
x = 6
I hope this helps, and have a great day!
Answer:
f(g(x)) = 9x^2 + 15x - 6
Step-by-step explanation:
We are using function g(x) = 3x - 1 as the input to function f(x) = x^2 + 7x.
Starting with f(x) = x^2 + 7x, substitute g(x) for x on the left side and likewise substitute x^2 + 7x for each x on the right side. We obtain:
f(g(x)) = (3x - 1)^2 + 7(3x - 1).
If we multiply this out, we get:
f(g(x)) = 9x^2 - 6x + 1 + 21x - 7, or
f(g(x)) = 9x^2 + 15x - 6
Answer:
B. (36, -12)
Step-by-step explanation: